Genetic analysis of consanguineous families presenting with congenital ocular defects. (May 2016) - Ullah, Ehsan; Nadeem Saqib, Muhammad Arif; Sajid, Sundus; Shah, Neelam; Zubair, Muhammad; Khan, Muzammil Ahmad; Ahmed, Iftikhar; Ali, Ghazanfar; Dutta, Atanu Kumar; Danda, Sumita; Lao, Richard; Ling-Fung Tang, Paul; et al.
Abstract: Anophthalmia and microphthalmia (A/M) are a group of rare developmental disorders that affect the size of the ocular globe. A/M may present as the sole clinical feature, but are also frequently found in a variety of syndromes. A/M is genetically heterogeneous and can be caused by chromosomal aberrations, copy number variations and single gene mutations. To date, A/M has been caused by mutations in at least 20 genes that show different modes of inheritance. In this study, we enrolled eight consanguineous families with A/M, including seven from Pakistan and one from India. Sanger and exome sequencing of DNA samples from these families identified three novel mutations including two mutations in the Aldehyde Dehydrogenase 1 Family Member A3 ( ALDH1A3 ) gene, [c.1310_1311delAT; p.(Tyr437Trp fs *44) and c.964G > A; p.(Val322Met)] and a single missense mutation in Forkhead Box E3 ( FOXE3 ) gene, [c.289A > G p.(Ile97Val)]. Additionally two previously reported mutations were identified in FOXE3 and in Visual System Homeobox 2 ( VSX2 ). This is the first comprehensive study on families with A/M from the Indian subcontinent which provides further evidence for the involvement of known genes with novel and recurrent mutations. Highlights: We enrolled eight consanguineous families affected with anophthalmia/microphthalmia from Pakistan and India. We performed Sanger sequencing of SOX2, ALDH1A3, OTX2, VSX2, RAX and FOXE3 in enrolled families. Sanger sequencing identified two novel mutations in ALDH1A3 and one novel mutation in FOXE3, solving three families. Sanger sequencing also identified a recurrent mutation in FOXE3 gene in two families. Whole exome sequencing was performed in two families, but the underlying causative mutation wasn't identified.